SUBSIDIARITY AND DEMOCRACY: SOURCES, CONTRADICTIONS, PROSPECTS OF CO-OPERATION - Панченко, Т.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The question of correlation of democracy and subsidiarity is ambiguous. These principles have general lines and distinctions. Thus the fate of subsidiarity is directly related to democracy and its conceptions – christian, deliberativе ones. In the conditions of becoming of multilevel political relations strengthening of subsidiarity democracy, which will provide distributing of plenary powers on the different levels of political co-operation, is expedient.